PLYOMETRIC EXERCISE DAPAT MENINGKATKAN SPEED LEBIH BAIKDIBANDINGKAN WARM-UP PADA PEMAIN SEPAK BOLA MUDA AMATIR - Agustiyawan, Agustiyawan; Pratama, Aditya Denny (UI Scholars Hub, 2019)
Football is a sport that requires a prime physical fitness level so that a football player can perform and reduce the risk of injury, so physical fitness level must be a serious concern especially for young players who are the seeds of the future of a soccer team and even a team national football. The aim of this study is to find out how much the physical fitness level increases for young amateur soccer players. This study used an experimental research method with a pre-test and post-test control group design research design that was given twice a week for 8 weeks in amateur soccer schools (SSB) in Tangerang with a total sample of 32 people with a treatment group of 16 people given warm -up for 15 minutes and plyometric exercise for 45 minutes, whereas in the control group a total of 16 people were given 45 minutes warm-up without plyometric exercise. Speed measurement test uses a 30 meter sprint. The results of this study show an increase in speed level in the treatment group with a value of 30 meters sprint (speed) 4.34 ± 0.51 seconds. This study shows that plyometric exercise can improve the physical fitness level of young amateur soccer players.